Does Training Toddlers in Emotion Knowledge Lead to Changes in Their Prosocial and Aggressive Behavior Toward Peers at Nursery?. Issue 4 (19th May 2017) - Ornaghi, Veronica; Brazzelli, Elisa; Grazzani, Ilaria; Agliati, Alessia; Lucarelli, Maria
ABSTRACT: Research Findings : Within the flourishing area of research demonstrating the efficacy of emotion-based interventions carried out by trained teachers in educational contexts in increasing children's emotional skills, this study makes an original contribution to the existing literature by focusing on the effects of this kind of intervention on toddlers' prosocial and aggressive behavior. Ninety-five 26- to 36-month-olds participated in a 2-month intervention in which trained teachers read emotion-based stories to small groups of children and then either involved them in conversations about emotions (experimental condition) or did not (control condition). Even after we controlled for age and general language ability, the children in the experimental condition were found to outperform the control group on measures of emotion knowledge and emotional-state talk. Furthermore, the intervention fostered gains in prosocial behavior, whereas it did not have a significant effect on the frequency of aggressive actions, which was lower at posttest in both groups. The positive effect of the training program on participants' prosocial behavior was no longer significant when we controlled for gains in emotion knowledge and emotional-state talk. Practice or Policy : The results encourage the implementation of early educational programs focused on emotion knowledge in order to foster children's prosocial behavior toward peers.